A scheme for forecasting severe space weather. Issue 3 (30th March 2017) - Balan, N.; Ebihara, Y.; Skoug, R.; Shiokawa, K.; Batista, I. S.; Tulasi Ram, S.; Omura, Y.; Nakamura, T.; Fok, M.‐C.
Abstract: A scheme is suggested and tested for forecasting severe space weather (SvSW) using solar wind velocity ( V ) and the north‐south component ( Bz ) of the interplanetary magnetic field (IMF) measured using the ACE (Advanced Composition Explorer) satellite from 1998 to 2016. SvSW has caused all known electric power outages and telegraph system failures. Earlier SvSW events such as the Carrington event of 1859, Quebec event of 1989 and an event in 1958 are included with information from the literature. Dst storms are used as references to identify 89 major space weather events ( Dst Min ≤ −100 nT) in 1998–2016. The coincidence of high coronal mass ejection (CME) front (or CME shock) velocity Δ V (sudden increase in V over the background by over 275 km/s) and sufficiently large Bz southward at the time of the Δ V increase is associated with SvSW; and their product (Δ V × Bz ) is found to exhibit a large negative spike at the speed increase. Such a product (Δ V × Bz ) exceeding a threshold seems suitable for forecasting SvSW. However, the coincidence of high V (not containing Δ V ) and large Bz southward does not correspond to SvSW, indicating the importance of the impulsive action of large Bz southward and high Δ V coming through when they coincide. The need for the coincidence is verified using the CRCM (Comprehensive Ring Current Model), which produces extreme Dst storms (< Dst MP > < −250 nT) characterizing SvSW when there is coincidence. Key Points: Coincidence of high CME front (or shock) velocity (Δ V ) and sufficiently large ‐ Bz corresponds to severe space weather (SvSW) Product (Δ V × Bz ) exhibiting a sharp negative spike exceeding a threshold can be used for forecasting SvSW that can cause power outage Coincidence of high V (not containing Δ V ) and ‐ Bz does not correspond to SvSW; importance of the coincidence is verified using CRCM Plain Language Summary: Severe space weather has been known to affect the society by damaging satellite systems and electric power grids. For example, a space weather of the type that occurred in September 1859, if occurs at present times, can cause very serious damages costing up to 1 to 2 trillion U.S. dollars. It is therefore important to study space weather and understand what determines the severity of space weather and whether it can be forecasted and predicted. In this paper we show that the coincidence of the speed of solar storms and southward orientation of the north‐south component of the interplanetary magnetic field is responsible for severe space weather at the Earth, and it can be forecasted by 35 min using the data from a satellite that stays at 220 × radius of Earth away from the Earth.